ANALISIS PERSEBARAN DAN KESESUAIAN LOKASI TEMPAT PEMBUANGAN SAMPAH DI KECAMATAN LUBUK KILANGAN KOTA PADANG - nurkharisma, ilham; chandra, deded (DEPARTEMEN GEOGRAFI FIS UNP, 2025)
Growth and changes of population for people's consumption patterns have make in an improve in the volume, types and increasingly diverse waste characteristics. The aim of this research is to find out how rubbish bins are distributed in Lubuk Kilangan District, Padang City and also the suitability of the location of rubbish dumps in Lubuk Kilangan District, Padang City. . This research included in quantitative descriptive research. Direct survey of TPS locations spread across Lubuk Kilangan District and processed using the ArcGis tool to describe the distribution of TPS locations. Based on the field observations results, it was found that the number of TPS was 6, namely (1). Tarantang Beringin TPS (2). Lemdadika Padang Basi (3). Bandar Buat /Simp. Gaduik (4). Indarung Municipal Corporation (5). Sako/Indarung and (6). Atap Genteng Indarung. The results of scoring and observation of the existing TPS show that the existing TPS which is spread across 6 location points in Lubuk Kilangan Subdistrict is in accordance with all TPS location suitability variables. However, there are still residential areas within the 500 m2 TPS service area that do not have TPS even though these areas have the potential for waste generation.